+0

# GELP ME

0
540
1

so i was stuck at a question and i dont know how to do it

6a + b = 16
5a - 2b = 19

Jun 17, 2015

#1
+20850
+10

6a + b = 16
5a - 2b = 19

$$\small\text{ \begin{array}{lrcl} (1) & 6a + b &=& 16 \qquad | \qquad -6a\\ & \mathbf{b} &=& \mathbf{16 -6a} \\ \\ \hline \\ (2) & 5a - 2b &=& 19 \qquad | \qquad \mathbf{b} = \mathbf{16 -6a}\\ & 5a -2(\mathbf{16 -6a}) &=& 19 \\ & 5a -32 + 12a &=& 19 \\ & 17a -32 &=& 19 \qquad | \qquad +32\\ & 17a &=& 19 +32\\ & 17a &=& 51 \qquad | \qquad :17\\ & a &=& \dfrac{51}{17} \\ & \mathbf{a} & \mathbf{=} & \mathbf{3} \\ \\ \hline \\ & b &=& 16- 6a \qquad | \qquad \mathbf{a} = \mathbf{3} \\ & b &=& 16 - 6 \cdot \mathbf{3} \\ & b &=& 16 - 18 \\ & \mathbf{b} &\mathbf{=} & \mathbf{-2} \\ \\ \hline \\ \end{array} }}$$

Jun 17, 2015

#1
+20850
+10

6a + b = 16
5a - 2b = 19

$$\small\text{ \begin{array}{lrcl} (1) & 6a + b &=& 16 \qquad | \qquad -6a\\ & \mathbf{b} &=& \mathbf{16 -6a} \\ \\ \hline \\ (2) & 5a - 2b &=& 19 \qquad | \qquad \mathbf{b} = \mathbf{16 -6a}\\ & 5a -2(\mathbf{16 -6a}) &=& 19 \\ & 5a -32 + 12a &=& 19 \\ & 17a -32 &=& 19 \qquad | \qquad +32\\ & 17a &=& 19 +32\\ & 17a &=& 51 \qquad | \qquad :17\\ & a &=& \dfrac{51}{17} \\ & \mathbf{a} & \mathbf{=} & \mathbf{3} \\ \\ \hline \\ & b &=& 16- 6a \qquad | \qquad \mathbf{a} = \mathbf{3} \\ & b &=& 16 - 6 \cdot \mathbf{3} \\ & b &=& 16 - 18 \\ & \mathbf{b} &\mathbf{=} & \mathbf{-2} \\ \\ \hline \\ \end{array} }}$$

heureka Jun 17, 2015